DOTP plasticizer continuous production process

CN122916840APending Publication Date: 2026-10-16ANHUI LITIAN ENVIRONMENTAL PROTECTION TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611004415.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-07
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

但现有生产工艺仍存在诸多技术瓶颈:一是常规催化剂活性较低,易残留在产品中影响色度、稳定性与电性能;二是传统催化剂载体比表面积小、活性位点分布不均,与催化剂结合力弱

Benefits of technology

[0021] 1. This invention addresses the challenges of separating and retaining homogeneous catalysts at the catalytic level through a synergistic design of a five-stage modified mesoporous nano-silica support and a chemically bonded loading of tetrabutyl titanate. The support undergoes alkaline etching for pore expansion, dual-silane composite modification, gradient activation, polyol hydroxylation, and trace zinc ion coordination modification, significantly increasing its specific surface area and pore regularity, and introducing abundant anchoring sites. This allows the tetrabutyl titanate to be firmly loaded through chemical bonding, rather than simple physical adsorption. This results in a significant improvement in the catalyst's high-temperature stability, preventing detachment under high-temperature and negative-pressure conditions during esterification, and ensuring consistently stable catalytic efficiency. This solves the problem of poor product color and decreased electrical performance caused by residue in traditional homogeneous catalysts. Simultaneously, it achieves efficient separation of the catalyst and product, significantly reducing titanium ion residue in the product and improving product purity and stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application relates to the technical field of plasticizers, and discloses a DOTP plasticizer continuous production process, which takes terephthalic acid and 2-ethylhexanol as raw materials and adopts a supported tetrabutyl titanate catalyst; the production process sequentially completes full-continuous procedures of continuous esterification, continuous negative-pressure dealcoholization, continuous water-washing-free neutralization, continuous negative-pressure dehydration, continuous one-time pressure filtration, continuous negative-pressure stripping, continuous vacuum drying and continuous finished product pressure filtration; alcohol-water azeotropic steam at the top of an esterification tower is automatically separated by condensation, and the octanol is closed-loop refluxed to the esterification system; the material after neutralization is directly dehydrated without water washing, so that continuous refining is realized; through the synergistic design of the five-stage modified mesoporous nanosilica carrier and the tetrabutyl titanate chemical bonding load, the problems of difficult separation and easy residue of the homogeneous catalyst are solved from the catalytic level, the titanium ion residue in the product is greatly reduced, and the product purity and stability are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of plasticizer technology, specifically a continuous production process for DOTP plasticizer. Background Technology

[0002] Plasticizers are indispensable modifiers in the processing of polymer materials such as plastics, rubber, and coatings. Among them, dioctyl terephthalate (DOTP) has become the mainstream green plasticizer to replace traditional phthalate esters due to its heat resistance, cold resistance, low volatility, excellent electrical insulation, and environmental friendliness (no phthalates). It is widely used in high-end products such as cable materials, artificial leather, and rigid films.

[0003] Currently, industrially produced DOTP is mostly made from purified terephthalic acid and 2-ethylhexanol through processes such as esterification, neutralization, water washing, de-alcoholization, drying, and filtration under the action of a catalyst. However, existing production processes still have many technical bottlenecks: First, conventional catalysts have low activity and are prone to remaining in the product, affecting color, stability, and electrical properties; second, traditional catalyst supports have small specific surface areas, uneven distribution of active sites, and weak binding force with the catalyst.

[0004] Therefore, developing a new DOTP production process with high catalyst activity, continuous operation throughout the entire process, low wastewater discharge without water washing, and stable and excellent product quality has significant industrial value and market demand. Summary of the Invention

[0005] To address the problems in the prior art, this invention provides a continuous production process for DOTP plasticizer.

[0006] The technical solution adopted by this invention to solve its technical problem is: a continuous production process for DOTP plasticizer, using purified terephthalic acid and 2-ethylhexanol as raw materials, and employing a supported tetrabutyl titanate catalyst; the supported catalyst is prepared by chemical bonding of tetrabutyl titanate with a five-level modified mesoporous nano silica carrier; the production process sequentially completes continuous esterification, continuous negative pressure de-alcoholization, continuous waterless neutralization, continuous negative pressure dehydration, continuous single-stage pressure filtration, continuous negative pressure stripping, continuous vacuum drying, and continuous finished product pressure filtration; the alcohol-water azeotropic vapor at the top of the esterification tower is automatically separated into water by condensation, and octanol is refluxed back to the esterification system in a closed loop; the neutralized material is directly dehydrated without water washing, thus achieving continuous purification.

[0007] As a further technical solution, the preparation method of the five-level modified mesoporous nano silica carrier is as follows:

[0008] (1) Mesoporous alkaline etching to expand pores: Take nano-silica with a particle size of 10~30nm and add it to 0.5mol / L sodium hydroxide aqueous solution at a solid-liquid ratio of 1:15g / mL. Stir at 85℃ for 1.5h, filter and wash with deionized water until neutral to obtain the pore-expanding carrier.

[0009] (2) Bissilane composite modification: The pore-expanding carrier was added to a 1:1 volume ratio of ethanol-toluene mixture at a solid-liquid ratio of 1:20 g / mL and ultrasonically dispersed for 30 min; the temperature was raised to 70℃ and a composite coupling agent accounting for 5% of the mass of the pore-expanding carrier was added dropwise. The composite coupling agent was KH-550 aminosilane and KH-560 epoxysilane at a mass ratio of 1:1. The mixture was stirred at a constant temperature for 3.5 h, filtered, and washed with anhydrous ethanol.

[0010] (3) Gradient high temperature activation: After vacuum drying, the modified product is heated to 400℃ at a heating rate of 5℃ / min, and activated at a constant temperature for 2h, and then naturally cooled to room temperature.

[0011] (4) Polyol hydroxylation: The activated carrier was immersed in a glycerol-water solution with a volume ratio of 1:2 at a solid-liquid ratio of 1:12 g / mL, refluxed at 105℃ for 2 h, filtered and washed with deionized water until neutral.

[0012] (5) Trace zinc ion coordination: The hydroxylated carrier was immersed in 0.01 mol / L zinc chloride aqueous solution at a solid-liquid ratio of 1:10 g / mL for 30 min at room temperature, filtered, washed with deionized water until no chloride ions were present, and dried under vacuum at 100℃ for 2 h to obtain the fifth-level modified mesoporous nano silica carrier.

[0013] As a further technical solution, the preparation method of the supported tetrabutyl titanate catalyst is as follows: a five-level modified mesoporous nano silica support is added to anhydrous 2-ethylhexanol at a solid-liquid ratio of 1:25 g / mL, ultrasonically dispersed for 45 min, tetrabutyl titanate is slowly added dropwise under nitrogen protection at 75-85℃, and the catalyst is chemically bonded and loaded at a constant temperature for 2 h. The free catalyst is then removed by filtration to obtain the catalyst.

[0014] As a further technical solution, the amount of the supported catalyst added is 0.05-0.08% of the mass of purified terephthalic acid.

[0015] As a further technical solution, in the continuous esterification process, the alcohol-acid molar ratio is 2.2-2.4:1, the reaction temperature is 180-200℃, the absolute reaction pressure is <10kPa, and the esterification endpoint acid value is ≤0.12mgKOH / g.

[0016] As a further technical solution, the vacuum degree of continuous negative pressure de-alcoholization and dehydration is 95-98 kPa and the bottom temperature of the column is 148-158℃; the vacuum degree of dehydration is 97-99 kPa and the bottom temperature of the column is 98-108℃.

[0017] As a further technical solution, in the continuous waterless washing neutralization process, the material temperature is 130-140℃, a 0.18-0.22% sodium carbonate solution is used as the neutralizing agent, the amount of calcium stearate nucleating agent added is 0.35-0.45‰ of the material mass, and the neutralization pressure is 0.55-0.65MPa.

[0018] As a further technical solution, in the continuous negative pressure stripping process, the vacuum degree is 97-99 kPa, the feed temperature is 155-165℃, the bottom temperature is 158-165℃, and the stripping steam volume is 7-9% of the material mass.

[0019] As a further technical solution, continuous vacuum drying is provided by a 2.0MPa steam jet pump with a vacuum degree of 98-99.5kPa. The alcohol content of the dried material is ≤150ppm, and the modified carrier is completely separated with the filter residue.

[0020] The beneficial effects of this invention are:

[0021] 1. This invention addresses the challenges of separating and retaining homogeneous catalysts at the catalytic level through a synergistic design of a five-stage modified mesoporous nano-silica support and a chemically bonded loading of tetrabutyl titanate. The support undergoes alkaline etching for pore expansion, dual-silane composite modification, gradient activation, polyol hydroxylation, and trace zinc ion coordination modification, significantly increasing its specific surface area and pore regularity, and introducing abundant anchoring sites. This allows the tetrabutyl titanate to be firmly loaded through chemical bonding, rather than simple physical adsorption. This results in a significant improvement in the catalyst's high-temperature stability, preventing detachment under high-temperature and negative-pressure conditions during esterification, and ensuring consistently stable catalytic efficiency. This solves the problem of poor product color and decreased electrical performance caused by residue in traditional homogeneous catalysts. Simultaneously, it achieves efficient separation of the catalyst and product, significantly reducing titanium ion residue in the product and improving product purity and stability.

[0022] 2. This invention employs a fully integrated continuous process encompassing continuous esterification, continuous negative pressure deethanolination, continuous waterless washing neutralization, continuous negative pressure dehydration, continuous stripping, and continuous vacuum drying. Combined with an automatic alcohol-water separation system at the top of the esterification tower and a closed-loop reflux structure for octanol, it achieves efficient raw material utilization and seamless process integration at the process level. During esterification, the alcohol-water azeotropic vapor is automatically separated, and octanol is directly refluxed back to the esterification system, reducing octanol loss and improving the stability of the alcohol-acid molar ratio. This promotes complete esterification and ensures the final acid value is stably controlled at a low level. Waterless washing neutralization uses a low-concentration sodium carbonate solution with a specialized calcium stearate nucleating agent to rapidly nucleate and neutralize acidic impurities under suitable temperature and pressure. This reduces the acid value to within acceptable limits without water washing, avoiding the large amounts of wastewater generated by washing, lowering environmental treatment costs, and eliminating saponification side reactions caused by washing, thus improving product yield. Simultaneously, continuous operation reduces manual intervention and parameter fluctuations, thereby solving the problems of unstable product quality and large batch-to-batch variations inherent in traditional processes.

[0023] 3. This invention utilizes a deep de-alcoholization and drying system with multi-stage negative pressure coordination, temperature gradient matching, and quantitative stripping steam, combined with high-vacuum drying using a 2.0MPa steam jet pump. This achieves deep removal of residual alcohol and ultimate product purification from a refining perspective. Due to the progressive optimization of vacuum and temperature in each unit of de-alcoholization, dehydration, stripping, and drying, and the precise matching of stripping steam volume with the material, the partial pressure of alcohol in the system is efficiently reduced without damaging the product structure. This rapidly removes free residual alcohol, ensuring the product's alcohol content remains consistently below 150ppm. Simultaneously, the modified carrier is completely separated from the filter residue during purification, further improving product transparency and volume resistivity. The overall solution organically integrates four core technologies: catalytic enhancement, continuous production, green waterless washing, and deep refining. This synergistic approach achieves the goals of high efficiency, low energy consumption, zero wastewater, and high quality in DOTP production. Key indicators such as product purity, acid value, color, residual alcohol, and volume resistivity are comprehensively superior to traditional processes, significantly improving the product's applicability in high-end cables and environmentally friendly polymer materials, and promoting the green and efficient development of the DOTP industry. Detailed Implementation

[0024] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0025] This invention provides a continuous production process for DOTP plasticizer, using purified terephthalic acid and 2-ethylhexanol as raw materials and employing a supported tetrabutyl titanate catalyst. The supported catalyst is prepared by chemical bonding of tetrabutyl titanate with a five-stage modified mesoporous nano silica carrier. The production process sequentially completes continuous esterification, continuous negative pressure deethanolination, continuous waterless neutralization, continuous negative pressure dehydration, continuous single-stage pressure filtration, continuous negative pressure stripping, continuous vacuum drying, and continuous finished product pressure filtration. The alcohol-water azeotropic vapor at the top of the esterification tower is automatically separated into water by condensation, and octanol is refluxed back to the esterification system in a closed loop. After neutralization, the material is directly dehydrated without water washing, achieving continuous purification.

[0026] This invention first prepares a five-level modified mesoporous nano-silica carrier, the preparation method of which is as follows:

[0027] (1) Mesoporous alkaline etching to expand pores: Take nano-silica with a particle size of 10-30nm and add it to 0.5mol / L sodium hydroxide aqueous solution at a solid-liquid ratio of 1:15g / mL. Stir at 85℃ for 1.5h, filter, and wash with deionized water until neutral to obtain the pore-expanding carrier.

[0028] (2) Bissilane composite modification: The pore-expanding carrier was added to a 1:1 volume ratio of ethanol-toluene mixture at a solid-liquid ratio of 1:20 g / mL and ultrasonically dispersed for 30 min; the temperature was raised to 70℃ and a composite coupling agent accounting for 5% of the mass of the pore-expanding carrier was added dropwise. The composite coupling agent was KH-550 aminosilane and KH-560 epoxysilane at a mass ratio of 1:1. The mixture was stirred at a constant temperature for 3.5 h, filtered, and washed with anhydrous ethanol.

[0029] (3) Gradient high temperature activation: After vacuum drying, the modified product is heated to 400℃ at a heating rate of 5℃ / min, and activated at a constant temperature for 2h, and then naturally cooled to room temperature.

[0030] (4) Hydroxylation of polyols: The activated carrier was immersed in a glycerol-water solution with a volume ratio of 1:2 at a solid-liquid ratio of 1:12 g / mL, refluxed at 105℃ for 2 h, filtered and washed with deionized water until neutral.

[0031] (5) Trace zinc ion coordination: The hydroxylated carrier was immersed in 0.01 mol / L zinc chloride aqueous solution at a solid-liquid ratio of 1:10 g / mL for 30 min at room temperature, filtered, washed with deionized water until no chloride ions were present, and dried under vacuum at 100℃ for 2 h to obtain the fifth-level modified mesoporous nano silica carrier.

[0032] The preparation method of the supported tetrabutyl titanate catalyst of the present invention is as follows: a five-level modified mesoporous nano silica support is added to anhydrous 2-ethylhexanol at a solid-liquid ratio of 1:25 g / mL, ultrasonically dispersed for 45 min, tetrabutyl titanate is slowly added dropwise under nitrogen protection at 75-85℃, and the catalyst is chemically bonded and loaded at a constant temperature for 2 h. The free catalyst is removed by filtration to obtain the catalyst.

[0033] The amount of the supported catalyst added is 0.05-0.08% of the mass of purified terephthalic acid.

[0034] In the continuous esterification process, the alcohol-acid molar ratio is 2.2-2.4:1, the reaction temperature is 180-200℃, the absolute reaction pressure is <10kPa, and the final acid value of esterification is ≤0.12mgKOH / g.

[0035] The continuous negative pressure dehydrogenation and dehydration processes have a dehydrogenation vacuum of 95-98 kPa and a bottom temperature of 148-158℃; and a dehydration vacuum of 97-99 kPa and a bottom temperature of 98-108℃.

[0036] In the continuous waterless neutralization process, the material temperature is 130-140℃, a 0.18-0.22% sodium carbonate solution is used as the neutralizing agent, the amount of calcium stearate nucleating agent added is 0.35-0.45‰ of the material mass, and the neutralization pressure is 0.55-0.65MPa.

[0037] In the continuous negative pressure stripping process, the vacuum degree is 97-99 kPa, the feed temperature is 155-165℃, the bottom temperature is 158-165℃, and the stripping steam volume is 7-9% of the material mass.

[0038] Continuous vacuum drying is provided by a 2.0MPa steam jet pump with a vacuum degree of 98-99.5kPa. The alcohol content of the dried material is ≤150ppm, and the modified carrier is completely separated with the filter residue.

[0039] DOTP reaction mechanism:

[0040] DOTP is produced by the reaction of terephthalic acid (PTA) and octanol in the presence of a non-acidic catalyst (tetrabutyl titanate), which proceeds in two steps as follows:

[0041] The first step involves the reaction of one molecule of octanol and one molecule of PTA to form a monoester, namely monooctyl terephthalate. The reaction equation is as follows:

[0042] The second step is to further react monooctyl terephthalate with octanol to produce dioctyl terephthalate, as shown in the following reaction formula:

[0043]

[0044] The overall reaction can be written as follows:

[0045]

[0046] One molecule of terephthalic acid reacts with two molecules of octanol to produce two molecules of dioctyl terephthalate and two molecules of water.

[0047] This invention combines a supported catalyst with a fully continuous process to achieve efficient and continuous production of DOTP plasticizers. The catalyst has high activity and is easy to separate, resulting in high product purity, low residue, no wastewater generation, and significantly improved production efficiency.

[0048] To further illustrate the present invention, the following embodiments will be described in detail.

[0049] Example 1:

[0050] Preparation of five-level modified mesoporous nano-silica carriers:

[0051] Mesoporous alkaline etching to expand pores: At a solid-liquid ratio of 1:15 g / mL, 10 nm nano-silica particles were added to a 0.5 mol / L sodium hydroxide aqueous solution, stirred at 85 °C for 1.5 h, filtered, and washed with deionized water until neutral to obtain the pore-expanding carrier.

[0052] Bissilane composite modification: The pore-expanding carrier was added to a 1:1 volume ratio of ethanol-toluene mixture at a solid-liquid ratio of 1:20 g / mL and ultrasonically dispersed for 30 min; the temperature was raised to 70℃, and a composite coupling agent accounting for 5% of the mass of the pore-expanding carrier was added dropwise. The composite coupling agent was KH-550 aminosilane and KH-560 epoxysilane in a mass ratio of 1:1. The mixture was stirred at a constant temperature for 3.5 h, filtered, and washed with anhydrous ethanol.

[0053] Gradient high-temperature activation: After vacuum drying, the modified product is heated to 400℃ at a heating rate of 5℃ / min, activated at a constant temperature for 2 hours, and then naturally cooled to room temperature.

[0054] Polyol hydroxylation: The activated carrier was immersed in a glycerol-water solution with a volume ratio of 1:2 at a solid-liquid ratio of 1:12 g / mL, refluxed at 105℃ for 2 h, filtered, and washed with deionized water until neutral.

[0055] Trace zinc ion coordination: The hydroxylated carrier was immersed in a 0.01 mol / L zinc chloride aqueous solution at a solid-liquid ratio of 1:10 g / mL for 30 min at room temperature, filtered, washed with deionized water until no chloride ions were present, and dried under vacuum at 100℃ for 2 h to obtain a five-stage modified mesoporous nano silica carrier.

[0056] Preparation of supported tetrabutyl titanate catalyst: Five-level modified mesoporous nano silica support was added to anhydrous 2-ethylhexanol at a solid-liquid ratio of 1:25 g / mL and ultrasonically dispersed for 45 min. Tetrabutyl titanate was slowly added dropwise under nitrogen protection at 75 °C and chemically bonded at a constant temperature for 2 h. Free catalyst was removed by filtration to obtain the supported catalyst.

[0057] Continuous production of DOTP plasticizers:

[0058] Continuous esterification: Using purified terephthalic acid and 2-ethylhexanol as raw materials, with an alcohol-acid molar ratio of 2.2:1, a supported catalyst of 0.05% by mass of purified terephthalic acid is added. The reaction temperature is 180℃, the absolute pressure of the reaction is less than 10kPa, and the acid value at the esterification endpoint is less than or equal to 0.12mgKOH / g. The alcohol-water azeotropic vapor at the top of the esterification tower is automatically separated by condensation, and octanol is refluxed back to the esterification system in a closed loop.

[0059] Continuous negative pressure dehydrogenation: dehydrogenation vacuum degree 95kPa, bottom temperature 148℃.

[0060] Continuous waterless neutralization: material temperature 130℃, 0.18% sodium carbonate solution as neutralizing agent, calcium stearate nucleating agent added at 0.35‰ of material mass, neutralization pressure 0.55MPa.

[0061] Continuous negative pressure dehydration: dehydration vacuum degree 97kPa, bottom temperature 98℃.

[0062] Continuous single-stage pressure filtration: removes large particulate impurities and catalyst residue from the material.

[0063] Continuous negative pressure stripping: vacuum degree 97kPa, feed temperature 155℃, bottom temperature 158℃, stripping steam volume is 7% of material mass.

[0064] Continuous vacuum drying: Vacuum is provided by a 2.0MPa steam jet pump, with a vacuum degree of 98kPa, and the material is dried until the alcohol content is less than or equal to 150ppm.

[0065] Continuous finished product pressure filtration: to obtain DOTP plasticizer finished product.

[0066] Example 2:

[0067] Preparation of five-level modified mesoporous nano-silica carriers:

[0068] Mesoporous alkaline etching to expand pores: At a solid-liquid ratio of 1:15 g / mL, nano-silica with a particle size of 30 nm was added to a 0.5 mol / L sodium hydroxide aqueous solution, stirred at 85 °C for 1.5 h, filtered, and washed with deionized water until neutral to obtain the pore-expanding carrier.

[0069] Bissilane composite modification: The pore-expanding carrier was added to a 1:1 volume ratio of ethanol-toluene mixture at a solid-liquid ratio of 1:20 g / mL and ultrasonically dispersed for 30 min; the temperature was raised to 70℃, and a composite coupling agent accounting for 5% of the mass of the pore-expanding carrier was added dropwise. The composite coupling agent was KH-550 aminosilane and KH-560 epoxysilane in a mass ratio of 1:1. The mixture was stirred at a constant temperature for 3.5 h, filtered, and washed with anhydrous ethanol.

[0070] Gradient high-temperature activation: After vacuum drying, the modified product is heated to 400℃ at a heating rate of 5℃ / min, activated at a constant temperature for 2 hours, and then naturally cooled to room temperature.

[0071] Polyol hydroxylation: The activated carrier was immersed in a glycerol-water solution with a volume ratio of 1:2 at a solid-liquid ratio of 1:12 g / mL, refluxed at 105℃ for 2 h, filtered, and washed with deionized water until neutral.

[0072] Trace zinc ion coordination: The hydroxylated carrier was immersed in a 0.01 mol / L zinc chloride aqueous solution at a solid-liquid ratio of 1:10 g / mL for 30 min at room temperature, filtered, washed with deionized water until no chloride ions were present, and dried under vacuum at 100℃ for 2 h to obtain a five-stage modified mesoporous nano silica carrier.

[0073] Preparation of supported tetrabutyl titanate catalyst: Five-level modified mesoporous nano silica support was added to anhydrous 2-ethylhexanol at a solid-liquid ratio of 1:25 g / mL and ultrasonically dispersed for 45 min. Tetrabutyl titanate was slowly added dropwise under nitrogen protection at 85 °C and chemically bonded at a constant temperature for 2 h. Free catalyst was removed by filtration to obtain the supported catalyst.

[0074] Continuous production of DOTP plasticizers:

[0075] Continuous esterification: Using purified terephthalic acid and 2-ethylhexanol as raw materials, with an alcohol-acid molar ratio of 2.4:1, a supported catalyst of 0.08% by mass of purified terephthalic acid is added. The reaction temperature is 200℃, the absolute pressure of the reaction is less than 10kPa, and the acid value at the esterification endpoint is less than or equal to 0.12mgKOH / g. The alcohol-water azeotropic vapor at the top of the esterification tower is automatically separated by condensation, and octanol is refluxed back to the esterification system in a closed loop.

[0076] Continuous negative pressure dehydrogenation: dehydrogenation vacuum degree 98kPa, bottom temperature 158℃.

[0077] Continuous waterless neutralization: material temperature 140℃, 0.22% sodium carbonate solution as neutralizing agent, calcium stearate nucleating agent added at 0.45‰ of material mass, neutralization pressure 0.65MPa.

[0078] Continuous negative pressure dehydration: dehydration vacuum degree 99kPa, bottom temperature 108℃.

[0079] Continuous single-stage pressure filtration: removes large particulate impurities and catalyst residue from the material.

[0080] Continuous negative pressure stripping: vacuum degree 99kPa, feed temperature 165℃, bottom temperature 165℃, stripping steam volume is 9% of material mass.

[0081] Continuous vacuum drying: Vacuum is provided by a 2.0MPa steam jet pump, with a vacuum degree of 99.5kPa, and the material is dried until the alcohol content is less than or equal to 150ppm.

[0082] Continuous finished product pressure filtration: to obtain DOTP plasticizer finished product.

[0083] Example 3:

[0084] Preparation of five-level modified mesoporous nano-silica carriers:

[0085] Mesoporous alkaline etching for pore expansion: At a solid-liquid ratio of 1:15 g / mL, nano-silica with a particle size of 20 nm was added to a 0.5 mol / L sodium hydroxide aqueous solution, stirred at 85 °C for 1.5 h, filtered, and washed with deionized water until neutral to obtain the pore expansion carrier.

[0086] Bissilane composite modification: The pore-expanding carrier was added to a 1:1 volume ratio of ethanol-toluene mixture at a solid-liquid ratio of 1:20 g / mL and ultrasonically dispersed for 30 min; the temperature was raised to 70℃, and a composite coupling agent accounting for 5% of the mass of the pore-expanding carrier was added dropwise. The composite coupling agent was KH-550 aminosilane and KH-560 epoxysilane in a mass ratio of 1:1. The mixture was stirred at a constant temperature for 3.5 h, filtered, and washed with anhydrous ethanol.

[0087] Gradient high-temperature activation: After vacuum drying, the modified product is heated to 400℃ at a heating rate of 5℃ / min, activated at a constant temperature for 2 hours, and then naturally cooled to room temperature.

[0088] Polyol hydroxylation: The activated carrier was immersed in a glycerol-water solution with a volume ratio of 1:2 at a solid-liquid ratio of 1:12 g / mL, refluxed at 105℃ for 2 h, filtered, and washed with deionized water until neutral.

[0089] Trace zinc ion coordination: The hydroxylated carrier was immersed in a 0.01 mol / L zinc chloride aqueous solution at a solid-liquid ratio of 1:10 g / mL for 30 min at room temperature, filtered, washed with deionized water until no chloride ions were present, and dried under vacuum at 100℃ for 2 h to obtain a five-stage modified mesoporous nano silica carrier.

[0090] Preparation of supported tetrabutyl titanate catalyst: Five-level modified mesoporous nano silica support was added to anhydrous 2-ethylhexanol at a solid-liquid ratio of 1:25 g / mL and ultrasonically dispersed for 45 min. Tetrabutyl titanate was slowly added dropwise under nitrogen protection at 80 °C and chemically bonded at a constant temperature for 2 h. Free catalyst was removed by filtration to obtain the supported catalyst.

[0091] Continuous production of DOTP plasticizers:

[0092] Continuous esterification: Using purified terephthalic acid and 2-ethylhexanol as raw materials, with an alcohol-acid molar ratio of 2.3:1, a supported catalyst of 0.065% by mass of purified terephthalic acid is added. The reaction temperature is 190℃, the absolute pressure of the reaction is less than 10kPa, and the acid value at the esterification endpoint is less than or equal to 0.12mgKOH / g. The alcohol-water azeotropic vapor at the top of the esterification tower is automatically separated by condensation, and octanol is refluxed back to the esterification system in a closed loop.

[0093] Continuous negative pressure dehydrogenation: dehydrogenation vacuum degree 96.5 kPa, bottom temperature 153℃.

[0094] Continuous waterless neutralization: material temperature 135℃, 0.20% sodium carbonate solution as neutralizing agent, calcium stearate nucleating agent added at 0.40‰ of material mass, neutralization pressure 0.60MPa.

[0095] Continuous negative pressure dehydration: dehydration vacuum degree 98kPa, bottom temperature 103℃.

[0096] Continuous single-stage pressure filtration: removes large particulate impurities and catalyst residue from the material.

[0097] Continuous negative pressure stripping: vacuum degree 98kPa, feed temperature 160℃, bottom temperature 162℃, stripping steam volume is 8% of material mass.

[0098] Continuous vacuum drying: Vacuum is provided by a 2.0MPa steam jet pump, with a vacuum degree of 98.5kPa, and the material is dried until the alcohol content is less than or equal to 150ppm.

[0099] Continuous finished product pressure filtration: to obtain DOTP plasticizer finished product.

[0100] Comparative Example 1:

[0101] Compared with Example 3, the difference is that: no five-level modified mesoporous nano silica carrier was used, and tetrabutyl titanate was directly used as the catalyst. The catalyst dosage was 0.065% of the mass of purified terephthalic acid. The rest of the production process and parameters were exactly the same as in Example 3.

[0102] Comparative Example 2:

[0103] Compared with Example 3, the difference is that the continuous waterless washing neutralization process is cancelled and the traditional water washing neutralization process is adopted. The rest of the production process and parameters are exactly the same as those in Example 3.

[0104] Comparative Example 3:

[0105] Compared with Example 3, the difference is that the octanol is not refluxed after the azeotropic vapor of alcohol and water at the top of the esterification tower is condensed and is directly discharged. The rest of the production process and parameters are exactly the same as those in Example 3.

[0106] Comparative Example 4:

[0107] Compared with Example 3, the difference is that the continuous negative pressure stripping and continuous vacuum drying processes are cancelled, and the finished product is obtained by only one pressure filtration. The rest of the production process and parameters are exactly the same as those in Example 3.

[0108] Experiment 1: Purity and acid value test of DOTP plasticizer products:

[0109] Experimental methods:

[0110] The acid value of the product was determined by potentiometric titration, and the purity of DOTP in the product was determined by gas chromatography. Each sample was tested in triplicate, and the average value was taken.

[0111] Experimental data:

[0112] Table 1

[0113] Example 1 0.098 99.52 Example 2 0.095 99.58 Example 3 0.092 99.61 Comparative Example 1 0.215 98.13 Comparative Example 2 0.146 99.05 Comparative Example 3 0.138 98.87 Comparative Example 4 0.182 98.46

[0114] The acid values ​​of Examples 1-3 were all less than 0.12 mg KOH / g, and the DOTP purity was higher than 99.5%, meeting the standards for high-quality DOTP plasticizers. Comparative Example 1, due to the use of unsupported tetrabutyl titanate, had low catalyst activity and poor dispersibility, resulting in incomplete esterification, a significant increase in acid value, and a significant decrease in product purity. Comparative Example 2 used water washing for neutralization, introducing moisture that led to localized side reactions, increasing acid value and decreasing purity. Comparative Example 3 did not reflux the esterified alcohol, resulting in decreased raw material utilization, incomplete reaction, and decreased purity. Comparative Example 4 lacked stripping and drying processes, leaving low-boiling-point impurities, increasing acid value, and decreasing purity.

[0115] Experiment 2: Test of residual alcohol content and catalyst separation rate in the product:

[0116] Experimental methods:

[0117] The residual amount of 2-ethylhexanol in the product was determined by headspace gas chromatography; the titanium content in the product was determined by inductively coupled plasma atomic emission spectrometry. The catalyst separation rate was calculated. Each sample was tested in parallel three times, and the average value was taken.

[0118] Experimental data:

[0119] Table 2

[0120] Example 1 126 0.85 99.21 Example 2 118 0.79 99.26 Example 3 112 0.72 99.32 Comparative Example 1 286 12.56 87.35 Comparative Example 2 195 0.81 99.18 Comparative Example 3 213 0.78 99.22 Comparative Example 4 425 0.75 99.25

[0121] In Examples 1-3, the residual alcohol content was less than 150 ppm, and the catalyst separation rate was higher than 99.2%, meeting product requirements. Comparative Example 1 used free tetrabutyl titanate, which was difficult to separate with the catalyst, had a high titanium content, and the residual alcohol could not be effectively removed, resulting in excessive levels. Comparative Example 2 introduced impurities during water washing and neutralization, interfering with the alcohol removal effect and increasing the residual alcohol content. Comparative Example 3's lack of alcohol reflux led to excessive alcohol residue, increasing the alcohol removal load and raising the residual alcohol level. Comparative Example 4 lacked stripping and drying processes, resulting in the inability to remove residual alcohol, with the content far exceeding the standard limit.

[0122] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A continuous production process for DOTP plasticizer, characterized in that, Using purified terephthalic acid and 2-ethylhexanol as raw materials, a supported tetrabutyl titanate catalyst is employed. The supported catalyst is prepared by chemical bonding of tetrabutyl titanate with a five-stage modified mesoporous nano silica support. The production process sequentially completes a full-continuous process including continuous esterification, continuous negative pressure deethanolination, continuous waterless neutralization, continuous negative pressure dehydration, continuous single-stage pressure filtration, continuous negative pressure stripping, continuous vacuum drying, and continuous finished product pressure filtration. The alcohol-water azeotropic vapor at the top of the esterification tower is automatically separated into water by condensation, and octanol is refluxed back to the esterification system in a closed loop. After neutralization, the material is directly dehydrated without water washing, achieving continuous purification.

2. The process according to claim 1, characterized in that, The preparation method of the five-level modified mesoporous nano silica carrier is as follows: (1) Mesoporous alkaline etching to expand pores: Take nano-silica with a particle size of 10~30nm and add it to 0.5mol / L sodium hydroxide aqueous solution at a solid-liquid ratio of 1:15g / mL. Stir at 85℃ for 1.5h, filter and wash with deionized water until neutral to obtain the pore-expanding carrier. (2) Bissilane composite modification: The pore-expanding carrier was added to a 1:1 volume ratio of ethanol-toluene mixture at a solid-liquid ratio of 1:20 g / mL and ultrasonically dispersed for 30 min; the temperature was raised to 70℃ and a composite coupling agent accounting for 5% of the mass of the pore-expanding carrier was added dropwise. The composite coupling agent was KH-550 aminosilane and KH-560 epoxysilane at a mass ratio of 1:

1. The mixture was stirred at a constant temperature for 3.5 h, filtered, and washed with anhydrous ethanol. (3) Gradient high temperature activation: After vacuum drying, the modified product is heated to 400℃ at a heating rate of 5℃ / min, and activated at a constant temperature for 2h, and then naturally cooled to room temperature. (4) Hydroxylation of polyols: The activated carrier was immersed in a glycerol-water solution with a volume ratio of 1:2 at a solid-liquid ratio of 1:12 g / mL, refluxed at 105℃ for 2 h, filtered and washed with deionized water until neutral. (5) Trace zinc ion coordination: The hydroxylated carrier was immersed in 0.01 mol / L zinc chloride aqueous solution at a solid-liquid ratio of 1:10 g / mL for 30 min at room temperature, filtered, washed with deionized water until no chloride ions were present, and dried under vacuum at 100℃ for 2 h to obtain the fifth-level modified mesoporous nano silica carrier.

3. The process according to claim 2, characterized in that, The preparation method of the supported tetrabutyl titanate catalyst is as follows: a five-level modified mesoporous nano silica support is added to anhydrous 2-ethylhexanol at a solid-liquid ratio of 1:25 g / mL, ultrasonically dispersed for 45 min, and tetrabutyl titanate is slowly added dropwise under nitrogen protection at 75-85℃. The catalyst is chemically bonded and loaded at a constant temperature for 2 h, and the free catalyst is removed by filtration to obtain the catalyst.

4. The process according to claim 3, characterized in that, The amount of the supported catalyst added is 0.05-0.08% of the mass of purified terephthalic acid.

5. The process according to claim 1, characterized in that, In the continuous esterification process, the alcohol-acid molar ratio is 2.2-2.4:1, the reaction temperature is 180-200℃, the absolute reaction pressure is <10kPa, and the final acid value of esterification is ≤0.12mgKOH / g.

6. The process according to claim 1, characterized in that, The continuous negative pressure dehydrogenation and dehydration processes have a dehydrogenation vacuum of 95-98 kPa and a bottom temperature of 148-158℃; and a dehydration vacuum of 97-99 kPa and a bottom temperature of 98-108℃.

7. The process according to claim 1, characterized in that, In the continuous waterless neutralization process, the material temperature is 130-140℃, a 0.18-0.22% sodium carbonate solution is used as the neutralizing agent, the amount of calcium stearate nucleating agent added is 0.35-0.45‰ of the material mass, and the neutralization pressure is 0.55-0.65MPa.

8. The process according to claim 1, characterized in that, In the continuous negative pressure stripping process, the vacuum degree is 97-99 kPa, the feed temperature is 155-165℃, the bottom temperature is 158-165℃, and the stripping steam volume is 7-9% of the material mass.

9. The process according to claim 1, characterized in that, Continuous vacuum drying is provided by a 2.0MPa steam jet pump with a vacuum degree of 98-99.5kPa. The alcohol content of the dried material is ≤150ppm, and the modified carrier is completely separated with the filter residue.